CYBER THREATS, VULNERABILITIES AND RISKS IN ECONOMIC SECTORS - Ibragimov Nodirjon Nusriddinovich; Askarova Nargiza Ilhomkhojayevna; Amirov Akbarshakh Dilshad son; Abdurakhmanov Vahid Abdumuqim son (Galaxy International Interdisciplinary Research Journal, 2022)
Terms such as cyberthreats, vulnerabilities, and risks are often used interchangeably and confused. This article aims to define each term, highlight how they differ, and show how they relate to each other.